Traditional games in central java coastal in improving the motor ability of early childhood - Indah Lestari; Richma Hidayati (Fakultas Ilmu Pendidikan UNP)
The traditional coastal games of Central Java have their own characteristics that are made and developed according to the cultural characteristics of the people of Central Java. Manufacturer games such as online games, video games began to replace the existence of traditional games, even the traditional game is considered as an ancient game, children prefer to choose a game from the factory that tend not to require physical movement excessive. Whereas if performing a traditional game, the child will need a thorough body movement for rough and smooth motor. For that it takes the understanding that precisely in the presence of motor movements of children or movement by the whole body of the child will provide development not only in the element of social maturity and brain enhancement of children to the fullest. But will be able to control the development of rough and smooth body movement of the children.